LEKSIKON ETNOMEDISIN BUBUS PADA PENUTUR BAHASA SASAK DI KECAMATAN KERUAK LOMBOK TIMUR - Pebriyanti, Baiq Sartika; Aswandikari, Aswandikari; Saharudin, Saharudin (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2025)
The research entitled " Lexicon Ethnomedicine Bubus for Sasak Language Speakers in Keruak District, East Lombok" aims to describe the lingual forms that mark the lexicon ethnomedicine bubus and the cultural views of the Sasak people in Keruak district. This type of research is qualitative research. Data was collected using observation and interview methods. Researchers conducted structured and non-structured observations and interviews in visits carried out in stages. Technically, this research utilizes componential analysis. From the research results it was found that the ethnomedicine lexicon of bubus in the form of siup-siup 'mixed ingredients' in making bubus consists of one element in the form of a noun word class, two elements in the form of a noun + noun word class, two elements consisting of a noun + adjective word class, and three elements consisting of the word class noun + noun + adjective/verb. Bubus ethnomedicines that are still used among the local community are bubus ulu, bubus rajê, bubus amar, bubus bidêdari ngamuk, bubus couples, and bubus têris nganak. Meanwhile, the community's view of bubus ethnomedicine is still considered as a very effective alternative medicine as a treatment for disease. strange, which people believe is caused by the actions of humans and ghost.